2004
DOI: 10.2343/geochemj.38.333
|View full text |Cite
|
Sign up to set email alerts
|

Rare earth element distribution in the acetic acid soluble fraction of combusted coals: Its implication as a proxy for the original coal-forming plants

Abstract: The precise concentrations of rare earth elements (REEs) in Japanese Ashibetsu and Taiheiyo coals, in Indonesian Ambalut coal, and in Australian boghead coal have been determined, in order to compare the REE contents of the coals with those of plants and also to obtain further knowledge of the original plants from which these coals were formed. By leaching the coals after ashing using a 10% acetic acid solution, each coal sample was separated into two fractions: an acetic acid soluble fraction, and an acetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…The peat profile from EGR also shows an increase of REE concentrations that corresponds to the beginning of the industrial period and increasing deposition of dust. Unlike soil-grown plants (Fu et al, 2001), peat mosses (Sphagnum) and grass (Carex) do not show a Ce anomaly in their REE patterns (Akagi et al, 2002;Fu et al, 2004). This is in agreement with a simple thermodynamic model (Akagi and Masuda, 1998) showing no possible formation of Ce anomaly at the low pH and E H found in peat bogs.…”
Section: Introductionsupporting
confidence: 82%
“…The peat profile from EGR also shows an increase of REE concentrations that corresponds to the beginning of the industrial period and increasing deposition of dust. Unlike soil-grown plants (Fu et al, 2001), peat mosses (Sphagnum) and grass (Carex) do not show a Ce anomaly in their REE patterns (Akagi et al, 2002;Fu et al, 2004). This is in agreement with a simple thermodynamic model (Akagi and Masuda, 1998) showing no possible formation of Ce anomaly at the low pH and E H found in peat bogs.…”
Section: Introductionsupporting
confidence: 82%
“…In hard coal, phosphate minerals, clay minerals and certain sulfides may act as potential REE carriers (Finkelman, 1982;Vassilev & Vasileva, 1996, 1997Ward et al, 1999;Ward, 2002;Willet et al, 2000;Worrall & Pearson, 2001;Yang & Zhou, 2001;Zhang et al, 2002). However, other studies have indicated that REE in coal may form a compound both with the organic and non-organic substance (Finkelman, 1982;Palmer et al, 1990;Schatzel & Stewart, 2003;Fu et al, 2004). The research of rare earth elements in coal has also indicated that HREE are characterized by a higher affinity with the organic substance of coal that the LREE (Eskenazy, 1987a, b;Dai et al, 2008Dai et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Rare earth elements in coal may provide information on the genesis and forming conditions of coal (Fu et al, 2004). The REE concentration in hard coal is variable and depends on its petrographic and mineral composition as well as the chemical properties (Smołka-Danielowska, 2010;Vassilev & Vassileva, 1996;Ward, 1999;Schatzel & Stewart, 2003;Pires & Querol, 2004;Zhang et al, 2004).…”
Section: Introductionmentioning
confidence: 99%